The impact of the problems facing Boeing on the corporate governance debate - Michalovič, Matej; Ali, Tanweer; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The recent problems that The Boeing Company is facing raised questions about company’s corporate governance. The common narrative says that these problems were ultimately caused by Boeing’s merger with McDonnell Douglas in 1997. The objective of the thesis is to assess how Boeing’s corporate governance practices evolved before and after the merger, and whether this evolution had an impact on the current problems that the company is facing. Main research methods of the thesis include longitudinal analysis of four corporate governance dimensions, together with qualitative assessment of the development of Boeing’s relationships with its stakeholders. The results show that after the merger, Boeing started to focus heavily on financial metrics and shareholder value maximization which negatively affected some of the key stakeholders. While focusing on shareholder value maximization, company’s decisions became short-term oriented, resulting in safety problems and ultimately in worse financial performance as well.
Vedoucí práce: Tanweer Ali
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses